RELEVANCE OF LEGAL ENTITY BAIT AT-TAMWIL (BT) BASED SYIRKAH FOR ISLAMIC BANK - Harahap, Burhanuddin; Hastuti, Luthfiyah Trini; Solikhah, Solikhah (Yustisia, 2016)
This study seeks to study the problems of incompatibility entities which exist in Indonesia.It is not compatible to the existing Islamic financial institutions in Indonesia because of differing philosophies. The problem studied is the barriers faced by Islamic banks regarding the necessity of Islamic banks incorporated limited liability company and the relevance of the legal entity Bait at-tamwil (BT) based syirkah for Islamic banks. Research methods used is an empirical law. It consists of research the legal identification and research on the effectiveness of the law.The type of data  are primary data and secondary data.The collection methods with interviews, focus group discussions and literature.Techniques of data analysis in this research  use the model interLawive analysis. The results showed that legal entity of the Limited Liability Company for Islamic banks are not suitable to meet the demands as stipulated in Islamic law. The Lawivities of Islamic banks are to meet the demands of sharia standards.Legal entity must be based on Islamic principles.It is not based on the principles of western culture where come from seculer perspective, limited liability company, individual, liberal and capital. Therefore the concept of a legal entity Bait at-Tamwil is very relevant to be legal entities Islamic banks which Islamic banks are really syar'i.